HUBUNGAN PENGETAHUAN PERSONAL HYGIENE DENGAN PERILAKU PERSONAL HYGIENE PADA ANAK USIA SEKOLAH DI SDN JATIREJO - Lidiya, Muwallidatul Maulidiyah (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran, 2024)
A state of complete physical, mental and social well-being, as defined by the World Health Organization (WHO), is necessary for a person to be considered healthy. Three domains of functioning—physical, psychological (cognitive and emotional), and social—are included in the assessment of health-related quality of life. There are many (multifactorial) aspects that influence a person's quality of life, and there are many complex issues in human research. Finding out how well the school-age children of SDN Jatirejo know about the topic of personal hygiene and how they practice it was the driving force for this research. Descriptive correlation is the research methodology used to investigate the relationships between variables in this cross-sectional study. This research looks at the dependent and independent variables at once, without taking into account time to see how these variables relate to each other. With 49 participants, the majority of whom had strong knowledge (48 out of 50, or 98%) about personal hygiene, this study found a correlation between students' knowledge and the hygiene practices they carried out while at school. 11. As many as 22.4% have sufficient knowledge. Although only one person had sufficient knowledge (2.0%) and his behavior was inadequate (2.0%), twenty-two people had sufficient knowledge (44.9% of the total) and fifteen people had insufficient knowledge (30.6% ).